The Contribution of Genetic Variation of Streptococcus pneumoniae to the Clinical Manifestation of Invasive Pneumococcal Disease. (17th May 2018) - Cremers, Amelieke J H; Mobegi, Fredrick M; van der Gaast–de Jongh, Christa; van Weert, Michelle; van Opzeeland, Fred J; Vehkala, Minna; Knol, Mirjam J; Bootsma, Hester J; Välimäki, Niko; Croucher, Nicholas J; Meis, Jacques F; Bentley, Stephen; et al.
Abstract : Knowledge of pneumococcal genotypic variants improved our clinical risk assessment for detrimental manifestations of invasive pneumococcal disease (IPD). This indicates that information on pneumococcal genotype is important for the diagnostic and treatment strategy in IPD. Abstract: Background: Different clinical manifestations of invasive pneumococcal disease (IPD) have thus far mainly been explained by patient characteristics. Here we studied the contribution of pneumococcal genetic variation to IPD phenotype. Methods: The index cohort consisted of 349 patients admitted to 2 Dutch hospitals between 2000–2011 with pneumococcal bacteremia. We performed genome-wide association studies to identify pneumococcal lineages, genes, and allelic variants associated with 23 clinical IPD phenotypes. The identified associations were validated in a nationwide (n = 482) and a post–pneumococcal vaccination cohort (n = 121). The contribution of confirmed pneumococcal genotypes to the clinical IPD phenotype, relative to known clinical predictors, was tested by regression analysis. Results: Among IPD patients, the presence of pneumococcal gene slaA was a nationwide confirmed independent predictor of meningitis (odds ratio [OR], 10.5; P = .001), as was sequence cluster 9 (serotype 7F: OR, 3.68; P = .057). A set of 4 pneumococcal genes co-located on a prophage was a confirmed independent predictor of 30-day mortality (OR, 3.4; P = .003). We could detect the pneumococcal variants of concern in these patients' blood samples. Conclusions: In this study, knowledge of pneumococcal genotypic variants improved the clinical risk assessment for detrimental manifestations of IPD. This provides us with novel opportunities to target, anticipate, or avert the pathogenic effects related to particular pneumococcal variants, and indicates that information on pneumococcal genotype is important for the diagnostic and treatment strategy in IPD. Ongoing surveillance is warranted to monitor the clinical value of information on pneumococcal variants in dynamic microbial and susceptible host populations.